Differences of Anxiety and Depression in Dry Eye Disease Patients According to Age Groups - Liu, Zhanglin; Sun, Shengshu; Sun, Xiaowen; Wu, Yuan; Huang, Yue (Frontiers in Psychiatry, 2022)
This study aimed to investigate the association between dry eye disease (DED) and DED-related anxiety and depression tendencies, as well as the risk factors for anxiety and depression in DED patients of different age groups. This was a cross-sectional study involving 160 DED patients and 80 healthy individuals aged 20-65. All participants completed the demographic characteristics investigation, Hospital Anxiety Depression Scale (HADS), Ocular Surface Disease Index (OSDI) questionnaire, Standard Patient Evaluation of Eye Dryness (SPEED) questionnaire, and underwent objective clinical eye examinations. In patients aged 20-40, anxiety and depression scores were correlated with OSDI, sleep disorders, and Best Corrected Visual Acuity. In DED patients aged 41‒65, anxiety scores were correlated with sleep disorders, level of DED impact on life and work, and severity of DED. Depression scores were correlated with sleep disorders and the severity of DED. The results indicated that the tendency for anxiety and depression was closely associated with DED and sleep disorders. Moreover, the factors affecting anxiety and depression in patients varied with age.